2002
DOI: 10.1111/j.1095-8649.2002.tb02411.x
|View full text |Cite
|
Sign up to set email alerts
|

Fluctuating asymmetries and reproductive success in the peacock blenny

Abstract: In an investigation of the relationship between reproductive success and fluctuating asymmetry (FA) in the peacock blenny Salaria pavo, FA was measured in four bilaterally paired characters in successful and unsuccessful males during the breeding season. Reproductive success among successful males was assessed by calculating the number of eggs the males were defending. Absolute FA values relative to trait size were high for all characters and it is suggested that this could be a consequence of sub-optimal envi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 41 publications
2
22
0
Order By: Relevance
“…Interestingly, previous field studies have failed to find any relation between the development of the crest and male reproductive success (Oliveira et al, 1999;Gonçalves et al, 2002), although larger males have been shown to be more successful in nature (Oliveira et al, 1999;Gonçalves et al, 2002). The present results suggest that one of the traits assessed by females during sexual interactions is the head crest.…”
Section: Discussionsupporting
confidence: 42%
See 1 more Smart Citation
“…Interestingly, previous field studies have failed to find any relation between the development of the crest and male reproductive success (Oliveira et al, 1999;Gonçalves et al, 2002), although larger males have been shown to be more successful in nature (Oliveira et al, 1999;Gonçalves et al, 2002). The present results suggest that one of the traits assessed by females during sexual interactions is the head crest.…”
Section: Discussionsupporting
confidence: 42%
“…The present results suggest that one of the traits assessed by females during sexual interactions is the head crest. In nature, males spent the majority of time with their head protruding from the nest while most of their body was inside (Oliveira et al, 1999;Gonçalves et al, 2002). Thus, the traits visually available for females to assess males should be located on the head.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the choices of males may rely on independent mechanisms, as in nature larger bourgeois males receive more eggs (Oliveira et al 1999;Gonçalves et al 2002). Associating with larger males should increase the probability of a sneaker participating in spawning events.…”
Section:  2003 the Association For The Study Of Animal Behaviour Pumentioning
confidence: 99%
“…Corroborating these results, in our experiment females preferred to associate and directed more courtship displays towards the male that had the larger crest. In the field, however, no relation between the development of the crest and the male's reproductive success has been demonstrated to date (Oliveira et al 1999;Gonçalves et al 2002a). These results suggest a female preference towards males with more developed crests, although in the field male choosiness and male-male competition for nest sites, with larger males having a higher reproductive success (Oliveira et al 1999;Gonçalves et al 2002a), probably dilutes the effect of this preference.…”
Section: Discussionmentioning
confidence: 39%